Alternatif Aplikasi Mudah Perpustakaan (Pengenalan Aplikasi ASP.Net ) - Indah, Rosiana Nurwa (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2019)
Introduction. Today we enter an era where the use of technology in everyday life is very natural. The use of this technology turned out to pose a challenge for information providers, one of them was the library. The library must be able to present information that collaborates with technology so that information can be conveyed effectively and efficiently to its users. One of them is by providing library websites using ASP.Net, which is server-side technology to develop web applications based on Microsoft .NET framework. Thus, libraries can create dynamic sites and web applications that are interactive, easy to use, easy to develop. Data Collection Method. In collecting data in this paper the writer uses data collection methods in the form of Results and Discussions. This article discusses the history of ASP. Net and its objects namely Namespace, Web Form, Basic Web Form Syntax, Class Page, Request Object, Respone Object, Server Object Conclusions. ASP.Net has many objects and is easy to use. Therefore, ASP.NET can be one of the recommendations for use in creating Web libraries